2017
DOI: 10.22159/ajpcr.2017.v10i11.19461
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenes From Ceriops Decandra (Griff.) W. Theob.

Abstract: Objective: To isolate and identify the chemical constituents of Ceriops decandra. Methods:The chemical constituents of C. decandra (Griff.) W. Theob. were isolated by silica gel chromatography. The structures of the isolated compounds were identified by nuclear magnetic resonance (NMR) spectroscopy.Results: Chemical investigation of the dichloromethane extracts of the leaves of C. decandra has led to the isolation of 3β-E-coumaroylbetulinic acid (1), lupeol fatty acid esters (2), betulonic acid (3), betulin (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…C. decandra is a salt tolerant plant and possesses unique bioactive metabolites. Lupane-triterpene esters and other triterpene constituents have been isolated from the leaves of C. decandra [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…C. decandra is a salt tolerant plant and possesses unique bioactive metabolites. Lupane-triterpene esters and other triterpene constituents have been isolated from the leaves of C. decandra [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The most promising approach in therapy is the use of natural substances with cytotoxic activity concerning tumor cells but not affecting healthy ones. Such substances include lupane triterpenoids-betulin, betulinic and betulonic acids and their derivatives [1][2][3][4][5][6][7]. Recent studies have shown that the combination of triterpenoids such as oleanolic, ursolic and betulinic acids with 5-fluorouracil might be a useful tool with reduced doses of an anticancer drug-5-fluorouracil and without any side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Lupane triterpenoids such as betulin (lup-20(29)-ene-3,28-diol) and its derivatives extracted from renewable natural resources [1][2][3], e. g. from birch bark, exhibit various types of pharmacological activity. The antioxidant, anti-inflammatory, hepatoprotective, antimutagenic, and other activities of the compounds were demonstrated by in vitro and in vivo experiments [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%